1985
DOI: 10.2307/3281430
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Baylisascaris procyonis to Illinois Raccoons (Procyon lotor)

Abstract: The gastrointestinal tracts of 310 steel-trapped or hunter shot Illinois raccoons (Procyon lotor) were collected in November and December 1979 and 1980 and examined for the presence of Baylisascaris procyonis (Nematoda) in order to determine the prevalence and intensity of this ascarid and to note any differences with respect to host age and sex. The raccoons were classified as either juveniles (animals less than 1 yr old) or adults. The prevalence for all the raccoons examined was 81.9% and is the highest rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Wise et al (7) and Shafir et al (8) did a breakdown of prevalence data presented elsewhere (1) and found that 58% of 3,967 raccoons examined in the midwestern United States were infected, 64% of 476 in the northeastern/mid-Atlantic region were infected, 4% of 1,868 in the Southeast region were infected, and 49% in the West/Southwest were infected. Most studies have reported a higher prevalence of the parasite in juvenile raccoons than in adult raccoons (1,9,64), although there are also reports where the ages (or genders) of infected animals did not significantly differ (65,66).…”
Section: Raccoons As Source Of Infectionmentioning
confidence: 94%
“…Wise et al (7) and Shafir et al (8) did a breakdown of prevalence data presented elsewhere (1) and found that 58% of 3,967 raccoons examined in the midwestern United States were infected, 64% of 476 in the northeastern/mid-Atlantic region were infected, 4% of 1,868 in the Southeast region were infected, and 49% in the West/Southwest were infected. Most studies have reported a higher prevalence of the parasite in juvenile raccoons than in adult raccoons (1,9,64), although there are also reports where the ages (or genders) of infected animals did not significantly differ (65,66).…”
Section: Raccoons As Source Of Infectionmentioning
confidence: 94%
“…Juveniles have a significantly higher prevalence of infection (93.5%) than adults (55.3%), the highest rate of egg shedding, and consequently a greater potential for environmental contamination (58). The higher parasite burden of juvenile raccoons (mean burden, 48 to 62 worms) than in adults (mean burden, 12 to 22 worms) likely reflects differences in mechanisms of infection (13,43,58 which stick to their mother's fur or contaminate the den and its surroundings (29,43). Adult raccoons, in contrast, ingest thirdstage larvae during predation or scavenging of infected intermediate hosts.…”
Section: Life Cyclementioning
confidence: 99%
“…Although the raccoons' residence or metal cages and soil possibly contaminated with ascarid eggs were thoroughly flamed by a portable propane torch, feces-contaminated wooden pedestals under metal mesh cages remained unflamed. Juvenile raccoons are known to be highly susceptible to ascarid infection [23,24]. Further, interruption of regular ascaricide treatment permitted luminal growth of B. procyonis that survived the first and/or second ascaricide treatment in the intestinal wall.…”
Section: Resultsmentioning
confidence: 99%